1,1 `-{[1,4-Phenylenebis(methylene)]bis(oxy)bis(3,1-phenylene)}diethanon e - Al-Mohammed, N.N.; Alias, Y.; Abdullah, Z.; Khaledi, H. (International Union of Crystallography, 2011)
In the title compound, C(24)H(22)O(4), the centroid of the central benzene ring lies on a special position of 2/m site symmetry, while the terminal aromatic rings are located on a mirror plane. The central and terminal benzene rings are perpendicular to each other. In the crystal, the molecules are connected via C-H center dot center dot center dot O hydrogen bonds into a three-dimensional polymeric structure. The network is further consolidated by a C-H center dot center dot center dot pi interaction.